(untitled) (Journal of Hama University, 2019)
Detecting breast tumors using microwave Imaging depends on the contrast in the electrical properties between the infected tissue and surrounding tissue when exposed to microwaves radiation. The purpose of this esearch is to develop a microstrip antenna working at 2.45GHz (within the industrial, scientific and medical frequency range ISM band) which is Capable to early detection of the tumor, so that the average energy absorbed by the breast tissue does not exceed the limit permitted by the Federal Communication Commission FCC. Three-dimensional structure has been formed for both breast tissue and tumor tissue based on the different values of conductivity, permittivity and mass density. Detection of the presence of the tumor is based on the presence of changes in the values of the current density and the rate of absorption of energy (SAR) in the tissues between the two cases (in the presence of the tumor and in the absence of it). In this research the location of a tumor with size 2mm is determined accurately by determining the coordinates ,corresponding to the location of the greatest absorption of the energy, within the breast tissue, the results indicate that the proposed antenna performance is accurate.